2017
DOI: 10.3844/ajbbsp.2017.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Silver Nanoparticles using Mediterranean Cypress (<i>Cupressus sempervirens</i>) Leaf Extract

Abstract: Silver nanoparticles (AgNPs) retained vast applications in science and technology. Due to the vast application of these particles in various disciplines, there is an interest for synthesis of AgNPs in an environmentally friendly and economic manner. For the first time we were used Mediterranean cypress (Cupressus sempervirens) leaf aqueous extract for biosynthesis of AgNPs. Prepared particles were in various shapes and their diameters were ranging from 10 to 80 nm. TEM micrographs were shown that AgNPs are cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 47 publications
(74 reference statements)
1
9
0
1
Order By: Relevance
“…Based on the TEM micrographs, INPs were heavily surrounded by biological components from leaf extract ( Figure S1), therefore, the resulting structure is a microstructure which composed of INPs and phytochemical compounds. Similar phenomenon is reported for the green synthesis of metal nanoparticles using a variety of plant extracts [16,23,49,50]. In some cases it has been confirmed that this biologic matrix is mainly composed of carbohydrates from leaf extract [23,49].…”
Section: Characterization Of Inpssupporting
confidence: 79%
“…Based on the TEM micrographs, INPs were heavily surrounded by biological components from leaf extract ( Figure S1), therefore, the resulting structure is a microstructure which composed of INPs and phytochemical compounds. Similar phenomenon is reported for the green synthesis of metal nanoparticles using a variety of plant extracts [16,23,49,50]. In some cases it has been confirmed that this biologic matrix is mainly composed of carbohydrates from leaf extract [23,49].…”
Section: Characterization Of Inpssupporting
confidence: 79%
“…Flavonoids are particularly interesting in this case due to their high antioxidant activity for medical purposes. Hydrophilic functional groups of various compounds surrounding nanoparticles make them colloid-stable in an aqueous medium [ 88 ]. Other interesting substances that act as reducing and stabilizing substances are the sucrose and fructose of garlic extract [ 89 ].…”
Section: Mechanism Of Silver Nanoparticles (Agnps) Biosynthesismentioning
confidence: 99%
“…Plant extracts are now vastly studied and used for the green synthesis of various nanostructures. The potential of extracts from different parts of plants such as leaf, fruit, flower, and seed is examined for the green synthesis of nanoparticles [3,[14][15][16][17][18][19]. In addition to plant extract, living plants have also the potential to perform green synthesis of nanoparticles, which means that some living plants are able to synthesize and maintain nanoparticles in their tissue.…”
Section: Introductionmentioning
confidence: 99%